La Certificación de Semillas y su Impacto en la Agrodiversidad, y en la Agricultura Indígena y Campesina - Arrobo Figueroa, Johnny Edison (2017)
The reforms to the 'Laws of Seeds', have become mechanisms of 'accumulation by dispossession'; Especially in agriculture in the global south. Intellectual property rights (IPR), registration laws and 'seed certification' are standards applied to living materials, tools that privatize germplasm and strip peasants of their seeds. Several academic disciplines describe these norms; However, the role of seeds in peasant and indigenous hands, Has not been addressed in depth. Considering their implication, the laws prohibit social and cultural practices, necessary for the operation of informal seed systems, which are not related to intellectual property issues. These laws cause more genetic erosion, end with sovereignty over seeds and eliminate agricultural biodiversity. In addition they establish as a requirement, certification and quality for the marketing and exchange of seeds; Regime that criminalizes their possession in agricultural communities. The theoretical approach from the Political Ecology provides the framework to investigate, analyze and explain the implications and scope of these laws. The current regulation and the new bill, provide the theoretical framework to understand: how? And because? These processes of regulation are given and, will lead to answer: Why seed certification and quality standards are introduced? The validity of laws, will serve to illustrate the argumentation; To conclude, the implications of these laws on the sovereignty of seeds are collected.